Blood gases of horses subjected to jugular vein occlusion during treadmill exercise - Dias, Deborah Penteado Martins; Da Silva, Marco Augusto Giannoccaro; Albernaz, Raquel Mincarelli; Gomide, Lina Maria Wehrle; Martins, Carla Braga; Bernardi, Nara Saraiva; Barbosa, José Carlos; De Queiroz-Neto, Antonio; De Lacerda-Neto, José Corrêa (Universidade Estadual de Londrina, 2016)
The purpose of the present investigation was to examine the effects of unilateral and bilateral jugular vein occlusion via temporary surgical ligature on arterial blood gases in horses during treadmill exercise. Six horses performed three exercise tests (ETs). ET1, considered to be the control, was performed in horses without jugular occlusion. ET2 and ET3 were performed in horses with unilateral and bilateral occlusion via temporary surgical ligature of the jugular veins, respectively. The partial pressure of oxygen (PO2) and partial pressure of carbon dioxide (PCO2) were determined. The PO2 showed decreased values during ET2 and ET3, suggesting that horses presenting acute jugular thrombophlebitis may have airflow limitations when exercising.
Keywords: Blood gases; Equine; Swan ganz; Thrombophlebitis; Upper airways